2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Disease Pandemic on the Number of Strokes and Mechanical Thrombectomies: A Systematic Review and Meta-Analysis

Abstract: Background This systematic review and meta-analysis aimed to evaluate the impact of the coronavirus disease (COVID-19) pandemic on stroke care, including the number of stroke alerts/codes, number of reperfusions, and number of thrombectomies during the pandemic compared to those during the pre-pandemic period. Methods A systematic literature search was performed using the PubMed, EuropePMC, and Cochrane Central databases. The data of interest were the number of strokes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
7
29
0
3
Order By: Relevance
“…Furthermore, the pandemic also interrupts dementia research 29 . Patients with dementia might be less able to communicate their medical concerns, and during the pandemic, a visit to hospital is often circumvented; 30,31 the caretakers should be aware to avoid possible delay if one requires urgent medical attention. Efforts should be pursued to mitigate the risk of infection in the community and nursing home, maintaining routine medical care, adapting research methodologies to the current situation, and beyond 32 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pandemic also interrupts dementia research 29 . Patients with dementia might be less able to communicate their medical concerns, and during the pandemic, a visit to hospital is often circumvented; 30,31 the caretakers should be aware to avoid possible delay if one requires urgent medical attention. Efforts should be pursued to mitigate the risk of infection in the community and nursing home, maintaining routine medical care, adapting research methodologies to the current situation, and beyond 32 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment, while 30 cases were reported to have large vessel occlusion, only 20 mechanical thrombectomies were performed. A comprehensive stroke center in Barcelona, Spain reported an 18 and 23% drop in the number of strokes codes and mechanical thrombectomies during the start of the pandemic, respectively, albeit without any changes in reperfusion and clinical outcomes (89) The World Stroke Organization recognizes the said difficulties and emphasizes the utility of telemedicine as well as best practice sharing to further optimize and streamline stroke processes (90,91).…”
Section: Discussionmentioning
confidence: 99%
“…As people continue to adjust to social distancing, a shift in the epidemiology of stroke and other medical conditions will most likely be observed, as is being seen in myocardial infarction [29] and in other countries [30][31][32][33][34][35][36][37] in the context of acute ischemic stroke. Although there is evidence to suggest a high rate of cerebrovascular complications in patients with SARS-CoV-2 infection [38][39][40][41][42][43], anecdotal reports indicate a falling rate of new ischemic stroke admissions [30][31][32]34,37,[44][45][46][47][48], stroke code activations [30,36,[49][50][51][52][53], imaging numbers [44,45], and diagnoses [45].…”
Section: Decrease In Ischemic Stroke Patientsmentioning
confidence: 99%
“…Additionally, decreases in acute ischemic stroke treatment numbers have been noted for both thrombolysis [ 46 , 53 , 56 , 57 ] and EVT [ 30 , 33 , 47 , 53 , 56 ], with an excellent meta-analysis presented by July et al [ 53 ], including data from nine studies [ 30 , 56 , 58 - 64 ]. Details of each of these studies, as well as other related studies [ 65 , 66 ], can be found in Table S2 ( Multimedia Appendix 1 ).…”
Section: Decrease In Ischemic Stroke Patientsmentioning
confidence: 99%
See 1 more Smart Citation